What has Harmonia axyridis to do with Dante’s Divine Comedy - Bozsik, András (Acta Agraria Debreceniensis, 2010)
The multicoloured Asian ladybird beetle (Harmonia axyridis (Pallas, 1773)), a former successful biological control agent in the USA and Western Europe became an invasive alien species threatening the diversity of native aphidophagous insects through competition and praying, a horticultural pest consuming various fruits and adversely affecting the wine quality and a human nuisance when occurring at high densities in buildings. Due to this dubious fame, attention has been paid to it also at national level which made inevitable to find for it a fitting name in different languages. In some cases and countries a version of the English name has been chosen however, regarding the meaning of this translated term in Hungarian, the try cannot be called fortunate. The objective of this contribution is to stress the function of common animal names in the Hungarian Sprachraum and to find a right and proper alternative with the help of etymology, mythology, classical literature, art (painting) and the experiences of Hungarian fruit and grape growers.